2009
DOI: 10.1084/jem.20090900
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-23 mediates Toxoplasma gondii–induced immunopathology in the gut via matrixmetalloproteinase-2 and IL-22 but independent of IL-17

Abstract: Peroral infection with Toxoplasma gondii leads to the development of small intestinal inflammation dependent on Th1 cytokines. The role of Th17 cells in ileitis is unknown. We report interleukin (IL)-23–mediated gelatinase A (matrixmetalloproteinase [MMP]-2) up-regulation in the ileum of infected mice. MMP-2 deficiency as well as therapeutic or prophylactic selective gelatinase blockage protected mice from the development of T. gondii–induced immunopathology. Moreover, IL-23–dependent up-regulation of IL-22 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
275
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 242 publications
(290 citation statements)
references
References 58 publications
12
275
0
3
Order By: Relevance
“…In infection with an attenuated strain of Salmonella enterica serovar Enteritidis, p19-deficient mice showed reduced survival and exacerbated liver necrosis only in the absence of IL-12 in an IL-17-independent manner [10]. In peroral infection with Toxoplasma gondii, which leads to the development of small intestine inflammation, the IL-23-dependent upregulation of IL-22 is essential for the development of ileitis; on the other hand, IL-17 is downregulated and dispensable [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In infection with an attenuated strain of Salmonella enterica serovar Enteritidis, p19-deficient mice showed reduced survival and exacerbated liver necrosis only in the absence of IL-12 in an IL-17-independent manner [10]. In peroral infection with Toxoplasma gondii, which leads to the development of small intestine inflammation, the IL-23-dependent upregulation of IL-22 is essential for the development of ileitis; on the other hand, IL-17 is downregulated and dispensable [11].…”
Section: Introductionmentioning
confidence: 99%
“…IL-22 has both proinflammatory/pathological and protective properties, depending on the inflammatory context [21]. The proinflammatory/pathological nature is apparent in mouse models with diseases such as psoriasis [4] and rheumatoid arthritis [22], and T. gondii infection [11]. In contrast, IL-22 plays protective roles and has tissue-protective and antimicrobial properties in several mouse models with diseases such as inflammatory bowel disease (IBD) [23], hepatitis [24] and infection with invading pathogenic bacteria [10,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that treatment with the synthetic selective gelatinase blocker RO28-2653 prevented Toxoplasma gondii-infected mice from hyper-acute Th1-type-driven pan-ileitis, a model mimicking immunopathological key features of Crohn's disease [17]. Furthermore, MMP-2-, but not MMP-9-deficient mice were protected from ileitis development [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is a heterodimeric molecule composed of p40 and p19 subunits [3]. The proinflammatory activities of IL-23 are responsible for the onset not only of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis [4,5], but also infection-induced pathological consequences of infection with the pathogens causing Lyme disease and toxoplasma encephalitis, for example [6,7]. The known biological roles for IL-23 in inflammation include induction of Th17-induced secretion of IL-17 [8] and suppression of CD4 + CD25 + Treg [9].…”
Section: Introductionmentioning
confidence: 99%